Lex sportiva: da autonomia jurídica ao diálogo transconstitucional - Negócio, Ramon de Vasconcelos (2011)
This work intends to study the lex sportiva s legal autonomy operation and its limits against another order, when there is a legal problem (specially constitutional) which is common to both of them. Right after this analysis, one will search for the possibilities of constructive interlacements orders, which will allow new perceptions according to typically constitutional questions. From the International Federations, it will be shown that the sportive law and its binding form are independent from the olympic context. However, together with the Olympic Movement, the World Anti-Doping Agency and the Court of Arbitration for Sport, it was possible to establish a bigger global legal- sportive order harmonization. This global characteristic is not rarely conflicting with other orders, which demanded the proper interlacement of, prominently, equality and freedom constitutional principles. The documentation analyzed composed by legal cases, Statutes and legislations (national, international and transnational) contributed also to give a new comprehension regarding sovereignty , constitutional procedures access and nationality , which will not only be limited to the national scope, but also transnational